2011
DOI: 10.1007/3418_2011_3
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Selective Oxidation by Multimetallic Active Sites of Polyoxometalate-Based Molecular Catalysts

Abstract: The catalytic oxidation is an area of the key technologies for converting petroleum-based feedstocks to useful chemicals such as diols, epoxides, alcohols, and carbonyl compounds. Many efficient homogeneous and heterogeneous oxidation systems based on polyoxometalates (POMs) with green oxidants such as H 2 O 2 and O 2 have been developed. This chapter summarizes the remarkable oxidation catalyses by POMs with multimetallic active sites. The multifunctionality of multimetallic active sites in POMs such as coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 195 publications
0
14
0
Order By: Relevance
“…into the vacant sites has been used to synthesize several metal-substituted POMs with controlled multinuclear active sites in both aqueous and organic media [7,11,23]. These molecular catalysts exhibit significant activity and selectivity for a wide range of reactions [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] [92][93][94].…”
Section: Transition-metal-substituted Polyoxometalatesmentioning
confidence: 99%
“…into the vacant sites has been used to synthesize several metal-substituted POMs with controlled multinuclear active sites in both aqueous and organic media [7,11,23]. These molecular catalysts exhibit significant activity and selectivity for a wide range of reactions [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] [92][93][94].…”
Section: Transition-metal-substituted Polyoxometalatesmentioning
confidence: 99%
“…Lacunary silicotungstates (SiW 11 ) have been the obvious choice for the study, especially acid catalysed reactions, because of the high stability of the fragmented lacunary species (73)(74)(75). Numbers of reports are available for synthesis and characterization of supported mono-lacunary silicotungstates (SiW 11 ); Lefebvre et al reported review covering synthesis of inorganic hybrid materials with encapsulated polyoxometalates in 2010 (76).…”
Section: Mono-lacunary Silicotungstatesmentioning
confidence: 97%
“…The POMs based on molybdenum, particularly, can act as effective catalysts for the H2O2-and O2-based green oxidations [15][16][17]. Furthermore, they are oxidatively stable and can undergo stepwise multi electron redox process without any structural modification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they are oxidatively stable and can undergo stepwise multi electron redox process without any structural modification. With transition-metalsubstituted POMs, it was reported that their remarkable catalytic activities were due to the multifunctional character of multimetallic active sites as simultaneous activation of oxidants and substrates, reaction intermediates stabilization, oxygen-transfer and multielectron transfer [15][16][17]. In previous studies, we have underlined the efficiency of transitionmetal-substituted POMs [18][19][20][21] as catalysts in the clean oxidation of cyclohexanone and mixture of cyclohexanone/cyclohexanol to adipic acid in the presence of hydrogen peroxide without solvent, phase-transfer agents and adding acid.…”
Section: Introductionmentioning
confidence: 99%